Defect characterisation in Cu2ZnSnSe4 kesterites via resonance Raman spectroscopy and the impact on optoelectronic solar cell properties. Issue 21 (17th May 2019) - Dimitrievska, Mirjana; Oliva, Florian; Guc, Maxim; Giraldo, Sergio; Saucedo, Edgardo; Pérez-Rodríguez, Alejandro; Izquierdo-Roca, Victor
Abstract : UV-based resonant Raman spectroscopy is an effective technique for a non-destructive assessment of defects in kesterite materials. Abstract : Polycrystalline kesterite Cu2 ZnSnSe4 (CZTSe) semiconductors have drawn attention as promising absorber candidates for the next generation of thin film photovoltaics. However, the narrow tolerance to stoichiometry variations, which favours the formation of secondary phases and cluster defects, is a challenging drawback that restrains the device performance. In this context Raman spectroscopy has been demonstrated to be a powerful tool for the characterization of CZTSe, allowing the assessment of relevant parameters such as structure, crystal quality and secondary phases. In this work, multiwavelength Raman scattering measurements using nine excitation wavelengths (from 325 to 1064 nm) were performed on CZTSe polycrystalline thin films in order to give a detailed identification of all the active Raman modes expected in this crystalline structure. The experimental results compare well with the vibrational properties that have been computed by first-principles calculations based on density functional theory. Calculations of the phonon density of states (PDOS), as well as the simulation of the Raman spectra, have allowed a better understanding of the experimentally observed vibrational modes. A "non-band gap resonant" Raman effect was observed under 325 nm excitation conditions, making ultra-violet (UV) Raman spectroscopy a very promising characterization technique due to its high sensitivity to the surface region which provides information on the buffer/absorber interface. Strong intensity enhancement of spectral regions around 176 cm −1 and 250 cm −1 is observed. Calculated PDOS and combinatorial experiments on more than 200 samples with stoichiometries close to the high efficiency device compositions lead to the correlation of these intensities with the concentration of VCu and ZnSn point defects, respectively. Correlation with the optoelectronic properties of the devices allowed identification of the optimal concentration of VCu and ZnSn point defects for the highest performance devices. The application of the presented methodology has been confirmed by performing the same Raman analysis on the CZTSe absorber with 11% device efficiency. This work demonstrates that defect engineering in CZTSe is of the foremost importance for the improvement of solar cell performance, and that UV-based Raman spectroscopy is an effective technique for the non-destructive assessment of defects in kesterite materials.